The impact of perceived work dirtiness on nursing students' professional commitment: the mediating role of career adaptability and the moderating role of social support - a cross sectional study - Chen Jilong; Tao Yueying; Chen Huizheng; Meng Yong; Li Genqiang (BMC, 2024)
Abstract Background Social consensus in the nursing industry is that the job is accompanied by dirtiness. It is generally accepted that negative cognition about a career is an important determinant in reducing nursing students' professional commitment. However, the impact of nursing students' perceived work dirtiness on professional commitment and its mechanism remains unclear. This study aimed to analyze the association between perceived work dirtiness and professional commitment and to examine the mediating role of career adaptability and the moderating role of social support among nursing students in mainland China. Methods A cross-sectional online study was conducted among 341 nursing students from three medical universities in Henan, China. The participants' perceived work dirtiness, career adaptability, professional commitment, and social support were obtained. SPSS 26.0 and Amos 23.0 software were used for the statistical analysis. Results Perceived work dirtiness was negatively related to career adaptability and professional commitment (P < 0.001). Career adaptability played a partial mediating role (β= -0.177, P < 0.001) in the relationship between perceived work dirtiness and professional commitment. Social support played a moderating role (β = 0.134, P < 0.01) in the relationship between perceived work dirtiness and career adaptability. Moreover, social support moderates the mediating role of career adaptability. Conclusions Nursing students' perceived work dirtiness is an important factor in reducing professional commitment. Therefore, nursing educators must enhance courses focusing on professional qualities, providing avenues for nursing students to access social support. This proactive approach aims to mitigate the adverse impact of perceived work dirtiness on professional commitment among nursing students.